Answer:
[tex]n = \frac{r}{\sqrt[nt]{\frac{a}{p}} -1 }[/tex]
Step-by-step explanation:
[tex]a=p(1+\frac{r}{n} )^{nt}[/tex]
[tex]\frac{a}{p} =(1+\frac{r}{n} )^{nt}[/tex]
[tex]\sqrt[nt]{\frac{a}{p}} =(1+\frac{r}{n} )[/tex]
[tex]\sqrt[nt]{\frac{a}{p}} -1 =(\frac{r}{n} )[/tex]
[tex]n = \frac{r}{\sqrt[nt]{\frac{a}{p}} -1 }[/tex]
[ Do not confuse, as there are 2 n's, one in subject and another as power. We can never make the power or in a root, the subject. In order to solve for n, we have to make the character "n", the subject. ]